5/6(1-3x)=4(-5x+2)

Simple and best practice solution for 5/6(1-3x)=4(-5x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6(1-3x)=4(-5x+2) equation:



5/6(1-3x)=4(-5x+2)
We move all terms to the left:
5/6(1-3x)-(4(-5x+2))=0
Domain of the equation: 6(1-3x)!=0
x∈R
We add all the numbers together, and all the variables
5/6(-3x+1)-(4(-5x+2))=0
We multiply all the terms by the denominator
-((4(-5x+2)))*6(-3x+1)+5=0
We calculate terms in parentheses: -((4(-5x+2)))*6(-3x+1), so:
(4(-5x+2)))*6(-3x+1
We add all the numbers together, and all the variables
-3x+(4(-5x+2)))*6(+1
Back to the equation:
-(-3x+(4(-5x+2)))*6(+1)
We add all the numbers together, and all the variables
-(-3x+(4(-5x+2)))*61+5=0
We move all terms containing x to the left, all other terms to the right
-(-3x+(4(-5x+2)))*61=-5

See similar equations:

| 2(c+3)=5(c-3) | | 2(u+5)=u | | |4y+-12|=2y | | 4t-35=-95-3t | | 75+15y=25y | | X+5/6x=10 | | 2/3(2t-7)+2/3t=-(95/3)-t | | 6c=c+25 | | -2a,-9=6a+15 | | (-0.4)=g/3-0.9 | | Z+36=3z | | x/8-1/2=1/2 | | 9-7(1+8k)=-35 | | 4(y+4)=12y | | y=4(-8)-18 | | y=6(-8)-2 | | 29-2x=5x+5 | | 28=4(7u) | | 28=4(9u) | | 28=4(4u) | | 2(3x+1-2)+x=12 | | 3x+4+3x+4+2x-1=79 | | 4x²+6x=-9 | | 4(17.5+-1.25y)+5y=70 | | 3x+4+3x+4+2x-1=180 | | 5y-3-9y=-25 | | 2(4x-1)+3=-7 | | X+12+2x-29+11x+1=180 | | 45+18-y=58 | | -40x+18+-20x+3+15x+9=180 | | 1200x+1000(1.5x)=2354400 | | 78-y=73 |

Equations solver categories